2021
DOI: 10.2166/wst.2021.512
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the role of treatment performance and soil characteristics of soil-based wastewater treatment systems

Abstract: Soil-based onsite wastewater treatment systems (OWTS) are becoming more important for the treatment and disposal of wastewater in areas that have not central wastewater collection and treatment systems. However, there are concerns that OWTS may have adverse effects on public health and environment. The purpose of this study is to treat wastewater with using natural soil column in order to evaluate treatment system performance. Wastewater was applied to two different natural soils at different flow rates of 9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…The degree of slope on which STS are situated and their proximity to a watercourse are highly transferable environmental variables and well recognised risk factors (Tyre et al, 2023;Wiesner-Friedman et al, 2022). Although the notion of effluent movement risk, represented by HOST in our study, makes the elicited proportions more representative of the UK, these can be modified to fit classifications of soils and associated hydrological pathways outside of the UK as a generalised concept (Baykus et al, 2022;Tamang et al, 2022). While the three risk factors integrated into our combined scenarios are recognised as key drivers of FIO risk (Glendell et al, 2018), the expert judgements provide only a first approximation of the likelihood of annual FIO delivery from STS to watercourses.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of slope on which STS are situated and their proximity to a watercourse are highly transferable environmental variables and well recognised risk factors (Tyre et al, 2023;Wiesner-Friedman et al, 2022). Although the notion of effluent movement risk, represented by HOST in our study, makes the elicited proportions more representative of the UK, these can be modified to fit classifications of soils and associated hydrological pathways outside of the UK as a generalised concept (Baykus et al, 2022;Tamang et al, 2022). While the three risk factors integrated into our combined scenarios are recognised as key drivers of FIO risk (Glendell et al, 2018), the expert judgements provide only a first approximation of the likelihood of annual FIO delivery from STS to watercourses.…”
Section: Discussionmentioning
confidence: 99%
“…TIỀM NĂNG Lọc đất từ lâu đã được sử dụng xử lý nước thải với chi phí thấp và loại bỏ chất dinh dưỡng hiệu quả. Theo các nghiên cứu trước đây, hệ thống lọc đất nhiều lớp (MSL: Multi-Soil-Layer) có thể loại bỏ hiệu quả nitơ, phốt pho và chất hữu cơ trong nước thải (Wakatsuki et al, 1993, Pattnaik et al, 2008, Baykuş and Karpuzcu 2021. Tuy nhiên, công nghệ này vẫn chưa được chấp nhận để xử lý nước thải ở nhiều vùng do những lo ngại đặc biệt về sự không ổn định trong việc loại bỏ vi khuẩn chỉ thị ô nhiễm phân.…”
Section: Công Nghệ Xử Lý Chi Phí Thấpunclassified
“…Research has shown that soil can naturally lter out certain things like COD, SS (Suspended Solids), phosphorus, and nitrogen. Natural soils can help to clean wastewater fast (Baykuş et al, 2022). A special type of soil called multilayer soil can effectively clean dirty water.…”
Section: Introductionmentioning
confidence: 99%